Invalidity of Arbitration Agreement Under the United Arab Emirates Law - TOUHBOUB, HEBA ZAIN (2017)
This dissertation discusses the Invalidity of Arbitration Agreement Under the United Arab Emirates Laws, as arbitration agreement is considered as the foundation stone of the arbitral process. Therefore, it is important to discuss the arbitration agreement and highlight the main conditions that help the parties to establish a valid arbitration agreement, it focus mainly on the cases that the parties should maintain to avoid having invalid agreement and in result a challenge of the arbitration award, which will delay the arbitral process and the enforcement of the arbitration award. This paper also includes arbitration and arbitration agreement definition, the features of arbitration as well as the differentiations between arbitration and other dispute resolution mechanisms such as mediation. The paper also aims to highlight the role the national courts in terms of the application of the invalidity of the arbitration award by presenting the procedures to submit such application to the court. Moreover, a recommendation to develop the efficiency of the court role regarding the invalidity of the arbitration award has been presented. This thesis addressed slightly the arbitration under the arbitration centers in the United Arab Emirates.